Tingkat Kepuasan Konsumen Terhadap Objek Wisata Pantai Nirwana Kota Baubau - Winda; Sadarun, Baru; Mansyur, Akhmad (Universitas Halu Oleo, 2021)
This study aims to determine the number and type of services for each tourist object and to determine the customer satisfaction level with the services of tourist object in Nirwana Beach, Baubau City. This research was conducted in August 2020. Data were obtained through distributing questionnaires, observation and documentation using accidental sampling technique with a total 60 respondents. The research variables observed were the number and type of services for each tourist object and the customer satisfaction level to each tourist object service at Nirwana Beach. Data were analyzed using qualitative descriptive analysis. The results of this study indicate that there are 3 types of tourist object services, namely service object games facility, services for beach attractions and services for supporting facilities. The customer satisfaction level is based on 5 dimensions of service quality, namely the satisfaction service level for game facility that get the highest rating, namely reliability with a range of 3.7 which indicates the criteria of being satisfied. The satisfaction service level of the beach attraction tourism object that gets the highest rating is physical evidence with a range 4.18 which shows being satisfied. The satisfaction service level of supporting facilities services which get the highest rating namely physical evidence of the canteen with a range of 4.55 which indicates very satisfied.